Sensoriamento remoto para análise de parâmetros de qualidade da água aplicado à piscicultura - Bartz , Rafael Luis (2021)
The use of technologies in rural areas has greatly contributed to improving agricultural processes and reducing rural exodus. In this context, fish farming stands out, which has been a source of income for many family farmers, who still lack technologies to assist in the daily management of the nurseries, especially with regard to monitoring water quality. The objective of this work was to create a tool to collect temperature and water transparency in excavated fish ponds, using remote sensing through remotely piloted aircraft (RPAS in the international acronym). Therefore, a prototype was developed consisting of 2 modules, which were coupled to an RPAS, with the purpose of collecting temperature and water transparency in real time during the flight, and sending data to an application developed for mobile devices such as smartphones or tablets, so that producers have an agile and easy way to measure these water quality parameters in their nurseries. Tests were carried out on a rural property in the city of Toledo - PR, and the developed system proved to be effective, optimizing the management of excavated ponds and contributing to the sustainability of fish farming, both economically, socially and environmentally, also contributing to sustainable development goals 2, 8, 9, 12 and 14 of the United Nations (UN).